Cholinergic Receptor and Cyclic Stretch-Mediated Inflammatory Gene Expression in Intact ASM - Kanefsky, Jeannette (American Thoracic Society, 2006)
We tested the hypothesis that cholinergic stimulation and cyclic stretch regulate inflammatory gene expression in intact airway smooth muscle by measuring mRNA expression in bovine tracheal smooth muscle using limited microarray analysis and RT-PCR. Carbachol (1 μM) induced significant increases in the expression of cyclooxygenase (COX)-1, COX-2, IL-8, and plasminogen activator, urokinase type (PLAU) to levels ranging from 1.3- to 3.1-fold of control. Sinusoidal length oscillation at an amplitude of 10% muscle length and a frequency of 1 Hz induced significant increases in the expression of CCL-2, COX-2, IL-1β, and IL-6 to levels ranging from 12- to 206-fold of control. Decreasing the oscillatory amplitude by 50% did not significantly change inflammatory gene expression. In contrast, decreasing the oscillatory frequency by 50% significantly attenuated inflammatory gene expression by 76–93%. Nifedipine (1 μM) had an insignificant effect on carbachol-induced gene expression, but significantly inhibited sinusoidal length oscillation-induced inflammatory gene expression by 40–78%. Correlation analysis revealed two groups of genes with differential responses to sinusoidal length oscillation. The highly responsive group included COX-2, IL-6, and IL-8, which exhibited 45- to 364-fold increases in gene expression in response to sinusoidal length oscillation. The moderately responsive group included CCL2 and PLAU, which exhibited 13- to 19-fold increases in gene expression in response to sinusoidal oscillation. These findings suggest that cyclic stretch regulates inflammatory gene expression in intact airway smooth muscle in an amplitude- and frequency-dependent manner by modulating the activity of L-type voltage-gated calcium channels.